The Concept of Law and Justice in Hamlet - Lamichhane, Bishwa Nath (Literary Studies, 2016)
This work strives to explore the concept of law, and justice in Hamlet, one of the greatest works of Shakespeare in the seventeenth century. According to Richard Posner “Law and literature are very old fields...” (5). So, this paper attempts to examine the question of Hamlet’s legal, political, legitimacy in his thought and action. It also tries to observe whether Claudius is a legitimate or illegitimate figurehead of the then existing state of Denmark. Hamlet, the greatest work of Shakespeare in the early modern age, portrays the protagonist sandwiched between the divine laws and Christian moral values and the practicality of human laws and the expediencies of present realities. The problem with Hamlet is what he calls in his soliloquy, ‘to be or not to be’ – ambivalence and procrastination in taking action. Hamlet represents a great legal dilemma. Hamlet tries to be perfect by observing both the natural law and justice and the existing human laws of the state. Hamlet is torn between the divine will, human reason and Christian moralities prohibiting taking revenge. The paper concludes with Hamlet’s tragic end as a consequence of his vacillation between the divine will and the human law. Hamlet mirrors jurisprudential dilemma.